A Two-Stage Enzymolysis Method and Its Application in Exerting Antioxidant Activity of Walnut Protein - Liu, Dandan; Chen, Min; Zhu, Junsong; Tian, Weijie; Guo, Yiting; Ma, Haile (Frontiers in Nutrition, 2022)
Traditional enzymolysis method for producing bioactive peptides does not consider the utilization of digestive enzymes in the human gastrointestinal tract, leading to the possibility of excessive hydrolysis and higher production cost. Therefore, a two-stage enzymolysis method was established in this study based on in vitro limited enzymolysis and gastrointestinal digestion, and applied it to the research of walnut protein (WP) in exerting antioxidant activity. Results showed that WP could be well digested by pepsin and pancreatin. WP with limited enzymolysis degree of 0% could achieve high antioxidant activity after the simulated gastrointestinal digestion, and the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and reducing power were 66.53% and 8.55 μmoL TE/mL, respectively. In vivo experimental results also exhibited that both WP and WP hydrolysate (WPH) could alleviate the oxidative damage induced by D-galactose in SD rats to some extent. Considering the digestive function of human body, in vitro limited enzymolysis, in vitro simulated gastrointestinal digestion and in vivo validation are necessary processes for the production of bioactive peptides.